A Nine-Level Switched-Capacitor Step-Up Inverter with Low Voltage Stress - Wang, Yaoqiang; Ye, Juncheng; Wang, Kaige; Nie, Fuquan; Li, Gen; Liang, Jun (Journal of electrical engineering & technology, 2023)
This paper proposes a nine-level switched-capacitor step-up inverter (9LSUI) which can achieve a quadruple voltage gain with single dc source. Differing from other switched-capacitor inverters, the voltage stress of switches is effectively reduced due to the elimination of H-bridge, and the peak inverse voltage of all switches is kept within 2 V dc . In addition, the proposed inverter is able to integrate inductive load, and the capacitor voltage self-balancing can be achieved without any auxiliary circuits. Moreover, the topology structure can be flexibly extended to raise the output levels, and the peak inverse voltage of switches can remain constant with the increase of sub-modules in the extended structure. Comprehensive comparisons are performed to verify the outstanding advantages of the proposed inverter. Finally, the steady-state and dynamic performance of the proposed inverter is validated through an experimental prototype, and the experimental results are provided to prove the theoretical analysis.